Kearifan Lokal Masyarakat Nelayan dalam Pengembangan Usaha Penangkapan Ikan dengan Teknologi Bagan Apung di Desa Pasir Putih, Kecamatan Lembo, Kabupaten Konawe Utara - Ridwan, Muhammad; Mukhtar, Mukhtar; Rahmah, Nur (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
Local knowledge refers to knowledge, belief, understanding or insight, as well as customs demanding human behavior in group life passed down from one generation to the next. Community fishing village of Pasir Putih has a deeply held beliefs relating to the manufacture of floating chart starting from the provision of construction tools, assembly charts, chart operation, until the process of harvesting and post-harvest. The purpose of this study was to describe the local wisdom that is in the fishing village of Pasir Putih communities on fishing effort by using technology and a floating chart to know the benefits of local wisdom fishing village of Pasir Putih subdistrict Lembo North Konawe.The research is a qualitative research, while the key informant in this study consists of 3 members, namely Mr. Puto Basirang as traditional leaders, Mr Asrul D, as village officials, and Mr. Abbas as fishermen. The location of this research is in the hamlet III, Pasir Putih subdistrict Lembo North Konawe. This research uses a model proposed by Miles and Huberman saying that activity in qualitative data analysis carried out intensively and continues through to the end so that the data is already saturated. The benefits that can be felt in preserving local wisdom passed down for generations, namely with the conservation of marine resources, the growing attitude of togetherness and mutual cooperation between the fishing community, the preservation of the balance of the marine ecosystem by not exploiting excessive and to keep the sea is not polluted.